Training & Sports - Kaiser S (Dynamic Media Sales Verlag, 2019)
Introduction: Calisthenics is a conditioning workout characterized by bodyweight exercises at bar and floor. Comparable to gymnastics or crossfit workouts, calisthenics demands a great amount of strength, coordination and flexibility. To date, no studies have examined injury rates among calisthenics participants.Methods: Utilizing a cross-sectional design, data were collected using an online-survey. The questionnaire was developed based on two validated assessment tools for sports and overuse injuries: a) the Oslo Sports Trauma Research Centre (OSTRC) Overuse Injury Questionnaire and b) the OSTRC Questionnaire in Health Problems. Data on training-specific aspects or location and type of injury-characteristics were assessed via standardized assessment tools. Results: In our sample (156 males and 28 females), 124 injuries from 72 people and 1.288 injuries per 1000 hours of training were reported. More than 70% of these injuries occurred at the upper extremity and were reported as muscle or tendon injury. Around 60% of all injuries led to a time-loss of training, ranging from one to 220 days (CI: [29.01; 51.27]).Discussion: Our sample showed a lower injury rate than sports with similar demands. Physicians, athletes, and trainers should be familiar with calisthenics-specific types of exercises and the related risk of injuries to build a basis for good treatment of injuries and a sufficient prevention strategy.KEY WORDS: Calisthenics, Turnen, Sportverletzung, Verletzungsrate, Trendsport